The relationship between working capital management and profitability of bumiputera-controlled companies in Malaysia - Fairuz Sofia, Kaharuddin (2018)
The relationship between working capital and profitability cannot be ignored because the improvement in the profitability is necessary for the survival of a firm. Therefore, the objective of this study is to investigate the relationship between working capital management and profitability of Bumiputera-controlled companies in Malaysia. The period of this study is from year 2006 until 2012. This study uses a panel data of ninety-four (94) Bumiputera companies listed on Kuala Lumpur Stock Exchange. Cash conversion cycle and its components are used as measures for working capital management. The main theory used is the trade-off theory. The trade-off theory provides support for manager’s trade-off between profitability and risk associated with the level of current asset and liabilities. Findings from the panel data regression analysis reveal that inventory conversion period and receivable collection period are significantly negatively correlated to profitability. This suggests that the shorter the period, the higher the profitability of Bumiputera-controlled companies tends to be. However, cash conversion cycle is significantly and positively correlated to profitability, suggesting that the longer the cash conversion period, the higher the profitability. The payable collection period is not significantly correlated to profitability. Finally, the study provides managerial implications, and suggests the direction for future research.